RESILIENSI DAN KEBAHAGIAAN DENGAN SOMATISASI PADA MAHASISWA TINGKAT AKHIR - Pujiarohman, Pujiarohman; Astuti, Indah Ayu Kusuma; Muslimah, Alfiana Indah (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45 Bekasi, 2024)
This study aims to determine the level of somatization, resilience and happiness, to find out there is a significant relationship between resilience and happiness with somatization, and to find out there is a significant effect between resilience and happiness with somatization in finalyear students at the Islamic University